Advanced technology of municipal solid waste conversion for a circular economy. Issue 1 (April 2021) - Lupu, M L; Isopescu, D N; Maxineasa, S G; Baciu, I-R; Antonescu, I; Cucos, I
Abstract: One of the most important environmental problems of the big urban areas is represented by the large volume of waste resulted from different human activities. In the last decades, different technologies have been developed to resolve this significant issue, and the most representative is the conversion of municipal solid waste (MSW) in different types of by-products. The first part of this paper presents the current state of plasma conversion technology that can be used for processing waste, and also, its potential in the construction sector which could be taken advantage of the by-products (syngas and slag) resulted from the plasma gasification of municipal solid waste (MSW), to enhance energy-efficiency in this domain. In the second part of the paper, there are analyzed different technologies for managing and processing municipal solid waste (MSW), which can be used nowadays, and the parameters, related to the costs, the period of use, the energy consumption and the environmental impact. All these aspects are compared with those of plasma conversion technology. The plasma conversion system can be commercialized successfully, and its costs can be reduced by generating income in the form of by-products and added-value in producing performant products in a circular economy.